2018
DOI: 10.1038/s41598-018-27416-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of intestinal cholesterol absorption, adipose energy expenditure and lipid handling by Sortilin

Abstract: The sorting receptor Sortilin functions in the regulation of glucose and lipid metabolism. Dysfunctional lipid uptake, storage, and metabolism contribute to several major human diseases including atherosclerosis and obesity. Sortilin associates with cardiovascular disease; however, the role of Sortilin in adipose tissue and lipid metabolism remains unclear. Here we show that in the low-density lipoprotein receptor-deficient (Ldlr−/−) atherosclerosis model, Sortilin deficiency (Sort1−/−) in female mice suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 57 publications
3
17
0
2
Order By: Relevance
“…Furthermore, studies on double knockout mice for the low-density lipoprotein receptor (Ldlr-/-, an atherosclerosis model) and sortilin (Sort1-/-) have confirmed the previous observations showing that sortilin is crucial for lipid homeostasis by suppressing intestinal cholesterol absorption mostly in female mice (Hagita et al, 2018). It is important to note that some contradictory results were obtained using another so-called sort1-/- model (Li et al, 2017a).…”
Section: Sortilin Is Associated To Distincts Ntsrs To Modulate Nt-medsupporting
confidence: 72%
See 2 more Smart Citations
“…Furthermore, studies on double knockout mice for the low-density lipoprotein receptor (Ldlr-/-, an atherosclerosis model) and sortilin (Sort1-/-) have confirmed the previous observations showing that sortilin is crucial for lipid homeostasis by suppressing intestinal cholesterol absorption mostly in female mice (Hagita et al, 2018). It is important to note that some contradictory results were obtained using another so-called sort1-/- model (Li et al, 2017a).…”
Section: Sortilin Is Associated To Distincts Ntsrs To Modulate Nt-medsupporting
confidence: 72%
“…It was observed that suppression of sortilin gene does not affect diet-induced obesity and glucose uptake from adipose tissue and skeletal muscle. A closer look of both Sort1-/- model mice used showed that the first studies were performed using a mouse in which the exon 14th of the sortilin gene was deleted, leading to the expression of a soluble sortilin receptor (Rabinowich et al, 2015; Hagita et al, 2018).…”
Section: Sortilin Is Associated To Distincts Ntsrs To Modulate Nt-medmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous evidence suggests that sortilin is implicated in the pathogenesis of many inflammatory and metabolic diseases, including T2DM and atherosclerotic complications of diabetes [31]. In addition, sortilin has been shown to be an energetic regulator of lipid metabolism [44]. No definitive data about the role of sortilin in atherosclerosis and diabetes, however, are available.…”
Section: Discussionmentioning
confidence: 99%
“…Linking risk factors of these diseases could identify molecular mechanisms that can be therapeutically targeted to lower cardiovascular risk in the increasing worldwide obese patient population. By supporting a connection of calcification genetic risk factors to obesity, we previously showed that a genetic risk factor for vascular calcification—sortilin—also contributed to obesity in a female mouse model of vascular disease ( 4 ). Whether similar connections between obesity and CAVD genetic risk factors exist is largely unknown.…”
mentioning
confidence: 76%